Algorithm to process the stepped frequency radar signal for a thin road surface application. (15th January 2018) - Hartikainen, Ari; Pellinen, Terhi; Huuskonen-Snicker, Eeva; Eskelinen, Pekka
Highlights: Corrections for stepped frequency continuous wave radar signal in frequency and time domain are proposed. Frequency–time transformations are done with customized inverse discrete Fourier transform. The automatic pipeline process can give results in real time. Abstract: This article describes an algorithm for calculating the relative permittivity from a stepped frequency continuous wave radar (SFCW) signal. The intended application for the developed radar is a quality estimation of the road surface layer, which includes homogeneity and density estimation. Automated fast computations are needed for road surveying purposes, which must be conducted alongside the normal traffic and with typical traffic speeds. For SFCW, we get N sweep waveforms for each sample point, where N equals the number of frequency steps, which poses a computational problem for onboard data acquisition. Radar signal processing steps are at first conducted in the frequency domain, where initial calibration corrections are applied. This data is then transferred to the time domain via inverse Discrete Fourier Transform. The relative permittivity is calculated from the peak produced by the surface reflection. A proof of the concept is given in the form of a pilot measurement on a real road. Results indicate that the automated signal detection algorithm is accurate enough to be used in real life measurements.